Molecular Phylogeny, Diversity, and Bioprospecting of Endophytic Fungi Associated with wild Ethnomedicinal North American Plant Echinacea purpurea (Asteraceae). Issue 7 (6th July 2016) - Carvalho, Camila R.; Wedge, David E.; Cantrell, Charles L.; Silva‐Hughes, Alice F.; Pan, Zhiqiang; Moraes, Rita M.; Madoxx, Victor L.; Rosa, Luiz H.
Abstract : The endophytic fungal community associated with the ethnomedicinal plant Echinacea purpurea was investigated as well as its potential for providing antifungal compounds against plant pathogenic fungi. A total of 233 endophytic fungal isolates were obtained and classified into 42 different taxa of 16 genera, of which Alternaria alternata, Colletotrichum dematium, and Stagonosporopsis sp. 2 are the most frequent colonizers. The extracts of 29 endophytic fungi displayed activities against important phytopathogenic fungi. Eight antifungal extracts were selected for chemical analysis. Forty fatty acids were identified by gas chromatography‐flame‐ionization detection (GC‐FID) analysis. The compounds (–)‐5‐methylmellein and (–)‐(3 R )‐8‐hydroxy‐6‐methoxy‐3, 5‐dimethyl‐3, 4‐dihydroisocoumarin were isolated from Biscogniauxia mediterranea EPU38CA crude extract. (–)‐5‐Methylmellein showed weak activity against Phomopsis obscurans, P . viticola, and Fusarium oxysporum, and caused growth stimulation of C. fragariae, C. acutatum, C. gloeosporioides, and Botrytis cinerea . (–)‐(3 R )‐8‐Hydroxy‐6‐methoxy‐3, 5‐dimethyl‐3, 4‐dihydroisocoumarin appeared slightly more active in the microtiter environment than 5‐methylmellein. Our results indicate that E. purpurea lives symbiotically with different endophytic fungi, which are able to produce bioactive fatty acids and aromatic compounds active against important phytopathogenic fungi. The detection of the different fatty acids and aromatic compounds produced by the endophytic community associated with wild E. purpurea suggests that it may have intrinsic mutualistic resistance against phytopathogen attacks in its natural environment. Abstract :